2022
DOI: 10.1002/cam4.4926
|View full text |Cite
|
Sign up to set email alerts
|

DPEP1 promotes drug resistance in colon cancer cells by forming a positive feedback loop with ASCL2

Abstract: Background Drug resistance is an important factor affecting the efficacy of chemotherapy in patients with colon cancer. However, clinical markers for diagnosing drug resistance of tumor cells are not only a few in number, but also low in specificity, and the mechanism of action of tumor cell drug resistance remains unclear. Methods Dipeptidase 1 (DPEP1) expression was analyzed using the cancer genome atlas (TCGA) and genotype‐Tissue Expression pan‐cancer data. Survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Profiles of overall survival (OS), disease-specific survival (DSS), disease-free interval (DFI), and progression-free interval (PFI) were obtained from TCGA survival data. The Prognostic outcome was visualized in the form of Kaplan–Meier (K-M) curves using the “survival” package ( Zeng et al, 2022 ) in R software (version 4.1.2), in which Cox’s proportional hazards model was generated as well to figure out whether FLT3 is an independent prognostic factor of BC. To be specific, univariate Cox regression analysis was used for the primary screening of the survival-related variables and only significant ones ( p < 0.05) would be included in the subsequent multivariable analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Profiles of overall survival (OS), disease-specific survival (DSS), disease-free interval (DFI), and progression-free interval (PFI) were obtained from TCGA survival data. The Prognostic outcome was visualized in the form of Kaplan–Meier (K-M) curves using the “survival” package ( Zeng et al, 2022 ) in R software (version 4.1.2), in which Cox’s proportional hazards model was generated as well to figure out whether FLT3 is an independent prognostic factor of BC. To be specific, univariate Cox regression analysis was used for the primary screening of the survival-related variables and only significant ones ( p < 0.05) would be included in the subsequent multivariable analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Surveying other gene signatures, we identified additional programs that coincided with IES such as pEMT and oxidative metabolism, which are hallmarks of advanced cancer and upregulated during tumor progression, validating the emergence of IES in late PPT (Figure 5C; Figure S5B). Moreover, fibrosis and hypoxia signatures correlated with IES at the patient-level, lending credence to the involvement of constituent genes in ECM signaling and regulation as these characteristics are implicated in microenvironmental immunosuppression 70,26,27,71,75 (Figure 5C; Figure S5D). Most importantly, this four-gene IES had a negative correlation with cytotoxic T cells (TL2) and with the CD8 T cell signature score across all tumor regions in the dataset, indicating its value as a predictor of immune exclusion 62 (Figure 5B).…”
Section: Resultsmentioning
confidence: 66%
“…The human NCM460 normal colon epithelial cell lines, the human colon cancer HCT116, RKO, LOVO, SW480, SW620 cell lines, and HEK293 cell lines were purchased from the Cell Bank at the Shanghai Institute of Cells, Chinese Academy of Sciences. All the cells were cultured at 37°C in 5% CO 2 19 …”
Section: Methodsmentioning
confidence: 99%
“…All the cells were cultured at 37°C in 5% CO 2 . 19 research revealed a novel mechanism by which the let-7b-5p-NKD1-APCβ-catenin signaling pathway inhibited colon cancer cell progression.…”
Section: Cell Culturementioning
confidence: 99%